Selective Histone Deacetylase Inhibitor ACY-241 (Citarinostat) Plus Nivolumab in Advanced Non-Small Cell Lung Cancer: Results From a Phase Ib Study - Awad, Mark M.; Le Bruchec, Yvan; Lu, Brian; Ye, Jason; Miller, JulieAnn; Lizotte, Patrick H.; Cavanaugh, Megan E.; Rode, Amanda J.; Dumitru, Calin Dan; Spira, Alexander (Frontiers in Oncology, 2021)
Background: Histone deacetylase (HDAC) overexpression has been documented in various cancers and may be associated with worse outcomes. Data from early phase studies of advanced non-small cell lung cancer (NSCLC) suggest encouraging antitumor activity with the combination of an HDAC inhibitor and either platinum-based chemotherapy or an EGFR inhibitor; however, toxicity is a limiting factor in the use of pan-HDAC inhibitors. Selective inhibition of HDAC6 may represent a potential therapeutic target and preclinical studies revealed immunomodulatory effects with HDAC6 inhibition, suggesting the potential for combination with immune checkpoint inhibitors. This phase Ib, multicenter, single-arm, open-label, dose-escalation study investigated the HDAC6 inhibitor ACY-241 (citarinostat) plus nivolumab in patients with previously treated advanced NSCLC who had not received a prior HDAC or immune checkpoint inhibitor. Methods: The orally administered ACY-241 dose was escalated (180, 360, or 480 mg once daily). Nivolumab was administered at 240 mg (day 15 of cycle 1, then every 2 weeks thereafter). The primary endpoint was to determine the maximum tolerated dose (MTD) of ACY-241 plus nivolumab. Secondary endpoints included safety, tolerability, and preliminary antitumor activity. Pharmacodynamics was an exploratory endpoint. Results: A total of 18 patients were enrolled, with 17 patients treated. No dose-limiting toxicities (DLTs) occurred with ACY-241 at 180 or 360 mg; 2 DLTs occurred at 480 mg. The MTD of ACY-241 was 360 mg. The most common grade ≥ 3 treatment-emergent adverse events were dyspnea (n = 3; 18%) and pneumonia (n = 3; 18%). At the 180-mg dose, 1 complete response and 2 partial responses (PR) were observed. At the 360-mg dose, 3 PRs were observed; 1 patient achieved stable disease (SD) and 1 experienced progressive disease (PD). At the 480-mg dose, no responses were observed; 1 patient achieved SD and 3 experienced PD. Acetylation analyses revealed transient increases in histone and tubulin acetylation levels following treatment. An increase in infiltrating total CD3+ T cells was observed following treatment. Conclusions: The study identified an MTD for ACY-241 plus nivolumab and the data suggest that the combination may be feasible in patients with advanced NSCLC. Responses were observed in patients with advanced NSCLC.